Complement and endothelial cell activation in COVID-19 patients compared to controls with suspected SARS-CoV-2 infection: A prospective cohort study - Bruni, Flavio; Charitos, Panteleimon; Lampart, Maurin; Moser, Stephan; Siegemund, Martin; Bingisser, Roland; Osswald, Stefan; Bassetti, Stefano; Twerenbold, Raphael; Trendelenburg, Marten; Rentsch, Katharina M.; Osthoff, Michael (Frontiers in Immunology, 2022)
Background Thromboinflammation may influence disease outcome in COVID-19. We aimed to evaluate complement and endothelial cell activation in patients with confirmed COVID-19 compared to controls with clinically suspected but excluded SARS-CoV-2 infection. Methods In a prospective, observational, single-center study, patients presenting with clinically suspected COVID-19 were recruited in the emergency department. Blood samples on presentation were obtained for analysis of C5a, sC5b-9, E-selectin, Galectin-3, ICAM-1 and VCAM-1. Results 153 cases and 166 controls (suffering mainly from non-SARS-CoV-2 respiratory viral infections, non-infectious inflammatory conditions and bacterial pneumonia) were included. Hospital admission occurred in 62% and 45% of cases and controls, respectively. C5a and VCAM-1 concentrations were significantly elevated and E-selectin concentrations decreased in COVID-19 out- and inpatients compared to the respective controls. However, relative differences in outpatients vs. inpatients in most biomarkers were comparable between cases and controls. Elevated concentrations of C5a, Galectin-3, ICAM-1 and VCAM-1 on presentation were associated with the composite outcome of ICU- admission or 30-day mortality in COVID-19 and controls, yet more pronounced in COVID-19. C5a and sC5b-9 concentrations were significantly higher in COVID-19 males vs. females, which was not observed in the control group. Conclusions Our data indicate an activation of the complement cascade and endothelium in COVID-19 beyond a nonspecific inflammatory trigger as observed in controls (i.e., “over”-activation).